Socio-economic impacts of landmines in southern Kurdistan - Heshmati, Almas (Cambridge Scholars, 2013)
The Kurdistan Region of Iraq has been massively contaminated by landmines and unexploded ordnance. This will continue to be a major obstacle for development and economic growth, particularly in the rural border communities. The mines were used systematica.